Cytotoxicity and chromatographic analysis of Dioon spinulosum, family Zamiaceae - Marwa Elghondakly, Abeer Moawad, Mona Hetta (Journal of Applied Pharmaceutical Science, 2020)
The identification of cytotoxic secondary metabolites from Dioon spinulosum Dyer ex. leaves was our aim. Thus, the evaluation of the cytotoxic activity of the total alcohol extract and successive fractions [n-hexane, dichloromethane (DCM), ethyl acetate, and n-butanol] against endocervix carcinoma (HeLa) and breast cancer (MCF7) cell lines was carried out using the sulforhodamine B assay. Identifying and authenticating D. spinulosum Dyer by DNA fingerprinting were carried out using Start Codon Translation (SCoT) and Inter simple Sequence Repeat, and revealed that SCoT4, SCoT6, SCoT8, HB-9, and HB-14 can be used for the identification of D. spinulosum at the genetic level. Chromatographic analysis and isolation, followed by the spectroscopic detection of the isolated compounds, were achieved by using various spectroscopic techniques. The following five compounds were isolated: β-sitosterol (1), 7,7'',4',4'''-O-tetra-methylamentoflavone (2), sciadopitysin (3), amentoflavone (4), and aromadendrin (5). Compounds 1 and 5 were obtained for the first time from the titled plant. This plant showed good cytotoxic activity against endocervix carcinoma as the total ethanolic extract, n-hexane, DCM, ethyl acetate, and n-butanol fractions showed IC50 values of 21.8, 21.1, 24.5, 26.5, and 21.4 μg/ml respectively, against HeLa cell lines. On the other hand, the total ethanolic extract and the fraction of ethyl acetate showed good anticancer activity against MCF7 cell line with IC50 values of 22.5 and 18 μg/ml, respectively. Aromadendrin showed IC50 = 12.5 μg/ml against MCF7 cell line. In conclusion, aromadendrin may be responsible for D. spinulosum cytotoxicity against breast cancer cell lines. The total extract exhibited a promising adjunctive therapy for anticancer patients with endocervix and breast carcinomas.
Keywords: Dioon spinulosum, endocervix carcinoma, breast cancer, biflavonoids, aromadendrin, DNA analysis.